Lived Experiences of The Recovery Process of People with Schizophrenia During a Pandemic - Dharma, I Dewa Gede Candra; Ahsan, Ahsan; Lestari, Retno (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The existence of social restrictions and activities during the pandemic in the last two years may have hampered the recovery process of people with schizophrenia. The Denpasar City Empowered House Rehabilitation Center is designed as a place for people with schizophrenia in the community to recover, become independent, and be productive. Several studies have attempted to explain how people with schizophrenia recover, but little is known about how this happens during pandemics. Therefore, this study used interpretive phenomenological methods to explore and understand the meaning of life for people with schizophrenia. The participants were 5 people with schizophrenia who were at the Denpasar Empowered House. Furthermore, interviews were conducted using in-depth techniques. The interview data were transcribed verbatim and analyzed using the Creswell approach. The results obtained 8 themes, namely: (1) Feeling cared for by others, (2) Accepted by the community, (3) Having a positive self-identity, (4) Ngayah helping the recovery process, (5) More helpful to explore self-ability, (6) To recover, (7) Enjoy active socializing, and (8) Situations that affect self-ability. It can be concluded that the participants interpret the recovery process as a goal to return to being part of the community during a pandemic.Abstrak: Adanya pembatasan dan aktivitas sosial selama pandemi dalam dua tahun terakhir dapat menghambat proses pemulihan penderita skizofrenia. Pusat Rehabilitasi Rumah Berdaya Kota Denpasar dirancang sebagai wadah bagi penderita skizofrenia di masyarakat untuk pulih, mandiri, dan produktif. Beberapa penelitian telah menjelaskan bagaimana penderita skizofrenia dapat pulih, tetapi sedikit yang diketahui tentang bagaimana proses pemulihan penderita terjadi selama pandemi. Oleh karena itu, penelitian ini menggunakan metode interpretif fenomenologis yang bertujuan untuk menggali dan memahami makna hidup bagi penderita skizofrenia. Partisipan adalah 5 orang penderita skizofrenia yang berada di Rumah Berdaya Denpasar. Selanjutnya, wawancara dilakukan dengan menggunakan teknik wawancara mendalam. Data wawancara ditranskripsikan secara verbatim dan dianalisis menggunakan pendekatan Creswell. Hasil yang diperoleh yaitu sebanyak 8 tema: (1) Merasa diperhatikan oleh orang lain, (2) Diterima oleh masyarakat, (3) Memiliki identitas diri yang positif, (4) Ngayah membantu proses pemulihan, (5) Lebih bermanfaat untuk mengeksplorasi kemampuan diri, (6) Untuk memulihkan diri, (7) Menikmati bersosialisasi secara aktif, dan (8) Situasi yang mempengaruhi kemampuan diri. Kesimpulan penelitian ini adalah penderita skizofrenia dapat memaknai proses pemulihan sebagai tujuan untuk kembali menjadi bagian dari masyarakat selama pandemi.